Aktivasi Pendengaran dan Penglihatan dalam Model Belajar Islami: Kajian Literatur - Ridha, Muhammad; Gade, Syabuddin (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2026)
This study aims to examine the activation of hearing and sight in Islamic learning models based on the perspective of Islamic education and various academic literature sources. In Islamic education, hearing (al-sam‘) and sight (al-abṣār) are regarded as fundamental human potentials that play an important role in acquiring knowledge, building character, and internalizing spiritual values. This study employed a qualitative approach using a library research method. Data were obtained through the exploration of journal articles, books, and scientific references related to audio-visual based Islamic learning models. The data analysis technique used content analysis through the stages of data reduction, theme categorization, interpretation, and conclusion drawing. The findings reveal that the activation of hearing plays a significant role in improving listening skills, understanding information, and strengthening the internalization of values through Qur’anic recitation, lectures, dialogue, and educational communication. Meanwhile, the activation of sight helps students understand concepts concretely through observation, visual media, demonstrations, and multimedia-based learning technologies. The integration of audio and visual approaches in Islamic learning has proven effective in enhancing students’ attention, motivation, memory, and emotional engagement in the learning process. Furthermore, this approach also supports character building, emotional development, and children’s spirituality through exemplary behavior, positive communication, and more interactive and meaningful learning experiences. This study concludes that the optimization of hearing and sight should become a primary concern in developing holistic and adaptive Islamic learning models in accordance with contemporary educational developments. Audio-visual approaches not only improve learning effectiveness but also strengthen moral formation and students’ religious awareness in their daily lives.